PENGARUH KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PADA CAFE AYAH BUNDA SITUBONDO DENGAN MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING - Amal, Moh Irsadul; Tulhusnah, Lusiana; Pramitasari, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing is generally seen as creating, introducing and delivering goods and services to consumers. Marketing is how companies create value for customers and build strong customer relationships to capture customer value. In return, marketing is an organizational function and set of processes for creating, communicating and delivering value to customers and managing customer relationships in ways that benefit the organization and its specific interests for customers of the Cafe Ayah Bunda in Mimbaan, Panji District, Situbondo Regency. This study aimed to analyze and test the effect of service quality and brand image on consumer satisfaction at Cafe Ayah Bunda, Situbondo, with consumer buying interest as an intervening variable. The population in this study are consumers at Cafe Ayah Bunda; the sampling method is determined by probability sampling. Data analysis and hypothesis testing in research using sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of this study indicate that service quality and brand image have a significant effect on consumer buying interest, service quality and brand image have a positive but not significant effect on customer satisfaction, purchase intention has a significant positive effect on consumer satisfaction, service quality and brand image have a significant positive effect on consumers satisfaction through consumer buying interest.